The European Union as a Manager of Global 'Business and Human Rights' Regulation: Country-by-Country Reporting Rules - Aleydis Nissen (UCL Journal of Law & Jurisprudence, 2019)
The European Union's 2013 Country-by-Country Reporting (CBCR) rules bring within the public domain information on corporate payments made to governments all over the world for the purpose of exploiting natural resources in the oil, gas, mining and logging sectors. In so doing, the CBCR rules enhance transparency in these sectors and aim to reduce tax avoidance and corruption in resource-rich countries. Arguably, they also contribute to the European Commission's long-term strategy to secure sustained access to raw materials in the European Economic Area. The CBCR rules represent one of the only three binding regulatory frameworks that have been adopted at the EU level to implement the 2011 UN Guiding Principles on Business and Human Rights. Just as with the two other initiatives that came into existence (the Non- Financial Reporting Directive and the Conflict Minerals Regulation), the immediate impact on the competitiveness of corporations based in the EU was a key concern during the legislative process. This article uncovers the two strategies that were employed to overcome such concern and give the CBCR rules a `global' character.
Keywords: O13; Q34; Q23; Q28; 330; CBCR; EITI; natural resources; transparency